Probing Surfactant Bilayer Interactions by Tracking Optically Trapped Single Nanoparticles - Jeonghyeon Kim; Olivier J. F. Martin (Advanced Materials Interfaces, 2023)
Abstract Single‐particle tracking and optical tweezers are powerful techniques for studying diverse processes at the microscopic scale. The stochastic behavior of a microscopic particle contains information about its interaction with surrounding molecules, and an optical tweezer can further facilitate this observation with its ability to constrain the particle to an area of interest. Although these techniques found their initial applications in biology, they can also shed new light on microscopic interface phenomena by unveiling nanoscale morphologies and molecular‐level interactions in real time, which are obscured in traditional ensemble analysis. Here, the application of single‐particle tracking and optical tweezers are demonstrated for studying molecular interactions at solid–liquid interfaces. Specifically, the surfactant behaviors at the water–glass interface are investigated by tracing gold nanoparticles that are optically trapped on these molecules. The underlying mechanisms governing the particle motion, which can be explained by hydrophobic interactions, disruptions, and rearrangements among surfactant monomers at the interfaces, are discovered. These interpretations are further supported by statistical analysis of an individual trajectory and comparison with theoretical predictions. The findings provide new insights into the surfactant dynamics and also illustrate the promise of single‐particle tracking and optical manipulation for studying nanoscale physics and chemistry of surfaces and interfaces.